Engaging Multidisciplinary Stakeholders to Drive Shared Decision-Making in Oncology. Issue 1 (January 2019) - Rocque, Gabrielle; Miller-Sonnet, Ellen; Balch, Alan; Stricker, Carrie; Seidman, Josh; Stiles, Susan; Ruggerio, John; Paynter, Nancy; Lewis, Mark; Kamal, Arif
Although recognized as best practice, regular integration of shared decision-making (SDM) approaches between patients and oncologists remains an elusive goal. It is clear that usable, feasible, and practical tools are needed to drive increased SDM in oncology. To address this goal, we convened a multidisciplinary collaborative inclusive of experts across the health-care delivery ecosystem to identify key principles in designing and testing processes to promote SDM in routine oncology practice. In this commentary, we describe 3 best practices for addressing challenges associated with implementing SDM that emerged from a multidisciplinary collaborative: (1) engagement of diverse stakeholders who have interest in SDM, (2) development and validation of an evidence-based SDM tool grounded within an established conceptual framework, and (3) development of the necessary roadmap and consideration of the infrastructure needed for engendering patient engagement in decision-making. We believe these 3 principles are critical to the success of creating SDM tools to be utilized both within and outside of clinical practice. We are optimistic that shared use across settings will support adoption of this tool and overcome barriers to implementing SDM within busy clinical workflows. Ultimately, we hope that this work will offer new perspectives on what is important to patients and provide an important impetus for leveraging patient preferences and values in decision-making.